Development and evaluation of culture media based on extracts of the cyanobacterium Arthrospira platensis - Kheirabadi, Elaheh; Macia, Javier (Frontiers in Microbiology, 2022)
Continuous advances in the fields of industrial biotechnology and pharmacy require the development of new formulations of culture media based on new nutrient sources. These new sources must be sustainable, high yielding, and non-animal-based, with minimal environmental impact. Thus, culture media prepared from cyanobacterial extracts can be an interesting alternative to the current formulations. In this study, we prepared various minimal formulations of culture media using the extracts of Arthrospira platensis, and analyzed the efficiency of these formulations, based on their effect on the production of biomass and molecules of industrial interest, using different types of bacteria. All media formulations prepared in this study showed better performance than conventional media, including those based on animal ingredients. Thus, based on their versatility and high-yielding capacity, we conclude that culture media prepared from cyanobacterial extracts are a good alternative to conventional media for meeting the current demands of the cosmetic and pharmaceutical industries.